Understanding the vicious cycle of myopic foresight and constrained technology deployment in transforming the European energy system - Jacob Mannhardt; Paolo Gabrielli; Giovanni Sansavini (iScience)
Summary: Short-term planning of myopic decision-makers jeopardizes the long-term energy transition, especially since constraints in deploying clean energy technologies further inhibit their rapid scale-up. Here, we show that the European energy transition followed myopic decision-making in the past and investigate how policy-based tools can secure the energy transition against myopic planning. Short-term decision-making in the European energy transition may fail to comply with climate goals and lead to substantial over-capacities. Carbon prices can only effectively internalize long-term climate goals if they account for constrained technology deployment, increasing to around 400 EUR/tCO2 in 2050. Idealized carbon prices, conversely, fail to incentivize the decarbonization of those sectors that stand at the beginning of their transition, such as renewable heating or carbon sequestration. Our exploration of myopic decision-making contributes to the understanding of the inhibiting barriers and bridges the gap between short-term decision-making and the long-term energy transition.